Lord of the Rakes - Wilde, Darcie (Berkley Sensation, 2014)
"All of London knows Philip Montcalm's name. It's on the lips of a different lady every night... So it's no wonder he's called the Lord of the Rakes. Rumor has it he's the most dangerous seducer in the city, with quite the extensive list of conquests. Talk of his prowess as a lover and his ingenuity in the bedroom are enough to make even the most prudish of ladies succumb to temptation. But as of late, Phillip has found himself a bit bored. Until he sets his eyes on a fiery newcomer. New to independence and London, gorgeous heiress Lady Caroline Delamarre wants to make the most of her life. And when Phillip meets her gaze, she knows the perfect place to start: in his arms...and in his bed. But what begins as a long night of breathtaking passion leads to more than the two bargained for. Haunted by troubled pasts and inescapable family entanglements, each of them must decide if they can risk a gamble on what might be true love."-- From back cover.